2018
DOI: 10.1002/jcp.27308
|View full text |Cite
|
Sign up to set email alerts
|

BI1 alleviates cardiac microvascular ischemia‐reperfusion injury via modifying mitochondrial fission and inhibiting XO/ROS/F‐actin pathways

Abstract: Pathogenesis of cardiac microvascular ischemia-reperfusion (IR) injury is associated with excessive mitochondrial fission. However, the upstream mediator of mitochondrial fission remains obscure. Bax inhibitor 1 (BI1) is linked to multiple mitochondrial functions, and there have been no studies investigating the contribution of BI1 on mitochondrial fission in the setting of cardiac microvascular IR injury. This study was undertaken to establish the action of BI1 on the cardiac microvascular reperfusion injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 69 publications
2
49
0
Order By: Relevance
“…In line with this finding, mitochondrial fission also plays a vital role in mediating cell death under IR injury [27]. Previous studies have shown that mitochondrial fission and fragmentation were markedly promoted in an IR-or H 2 O 2 -induced oxidative stress model and repressed mitochondrial fission through inhibiting Drp1 activity-attenuated IR-induced cell death [27,28,[58][59][60]. Consistent with previous findings, our results showed that t-BHP-induced oxidative stress promoted mitochondria fission and cell apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…In line with this finding, mitochondrial fission also plays a vital role in mediating cell death under IR injury [27]. Previous studies have shown that mitochondrial fission and fragmentation were markedly promoted in an IR-or H 2 O 2 -induced oxidative stress model and repressed mitochondrial fission through inhibiting Drp1 activity-attenuated IR-induced cell death [27,28,[58][59][60]. Consistent with previous findings, our results showed that t-BHP-induced oxidative stress promoted mitochondria fission and cell apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…NR4A1 induces Mff phosphorylation and enhances Drp1 recruitment onto mitochondria [135], leading to mitochondrial fragmentation. In contrast, BI-1 interrupts the ROS-mediated mitochondrial damage and partly blocks mitochondrial fission-induced endothelial cell death [131,136]. However, the relationship between mitochondrial fission and oxidative stress and the threshold of physiological mitosis shift to fatal mitochondrial fission require further investigation.…”
Section: Mitochondrial Fissionmentioning
confidence: 97%
“…Once positioned on the outer mitochondrial membrane, Drp1 interacts with four mitochondrial-bound proteins that serve as Drp1 receptors (mitochondrial dynamic proteins of 49 and 51 kDa (Mid49 and Mid51), mitochondrial fission protein 1 (Fis1), and mitochondrial fission factor (Mff), where it constricts and cleaves the mitochondria [122] (Figure 2). (NR4A1) [135] or Bax inhibitor-1 (BI-1) [131,136], respectively. NR4A1 induces Mff phosphorylation and enhances Drp1 recruitment onto mitochondria [135], leading to mitochondrial fragmentation.…”
Section: Mitochondrial Fissionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER also exerts a critical effect on protein generation, synthesis, modification and transport [11][12][13]. The primary result of ER dysfunction is ER stress, an effect that is accompanied with an accumulation of misfolded proteins and calcium overloading [14,15]. Subsequently, disruption of calcium homeostasis has been found to be associated with oxidative stress that contributes to the activation of apoptosis in a mechanism through ER stress [3,16].…”
Section: Introductionmentioning
confidence: 99%